Anti-inflammatory and cytotoxic components from Dichrocephala integrifolia. (June 2015) - Lee, Chia-Lin; Yen, Ming-Hon; Hwang, Tsong-Long; Yang, Juan-Cheng; Peng, Chieh-Yu; Chen, Chao-Jung; Chang, Wen-Yi; Wu, Yang-Chang
Graphical abstract: Highlights: Bioactive components of Dichrocephala integrifolia were investigated. Eleven compounds including three new ones were isolated from D. integrifolia . Two diterpenoids exhibited potent antineutrophilic inflammation. Two sinapyl alcohols showed moderate cytotoxicity properties. ABSTRACT: Portulide glucoside A (1 ), 14-acetoxy-9- epi -britanlin A (2 ), and dichroditerpene A (3 ) along with eight known compounds were isolated from Dichrocephala integrifolia . Diterpenoids 3 and 5 showed antineutrophilic inflammatory activities against not only superoxide anion generation with IC50 values of 1.74 and 4.40 μM, but also elastase release with IC50 values of 1.32 and 3.67 μM, respectively. Additionally, sinapyl alcohols 8 and 9 showed moderate cytotoxicity toward DU145 human prostate cancer cell line with IC50 values of 24.1 and 19.0 μM, respectively. Isolates 1–10 were found for the first time in this plant.